Sexual Dysfunction and Sex Hormone Abnormalities in Patients With Cirrhosis: Review of Pathogenesis and Management. Issue 6 (14th May 2019) - Neong, Shuet Fong; Billington, Emma O.; Congly, Stephen E.
Abstract : Healthy sexual function is important to maintain a good quality of life but is frequently impaired in patients with cirrhosis. The degree of sexual dysfunction appears to be linked with the degree of hepatic dysfunction. In men, sexual dysfunction can be related to the hyperestrogenism of portal hypertension and/or to decreased testosterone resulting from testicular dysfunction. In women, suppression of the hypothalamic–pituitary–gonadal axis appears to be a principal contributor, with no significant effect of portal hypertension. There is also a huge psychological barrier to break through as there is a component of depression in many patients with cirrhosis. Sexual dysfunction is often underdiagnosed in the cohort with cirrhosis. Management of sexual disorders in patients with cirrhosis can be challenging as they are often multifactorial. A multidisciplinary approach is key in managing these patients. We review the current literature on the pathogenesis of sexual dysfunction in patients with cirrhosis and propose a stepwise algorithm to better manage these patients.